2019
DOI: 10.3390/atmos10120771
|View full text |Cite
|
Sign up to set email alerts
|

Emission Factors for Biofuels and Coal Combustion in a Domestic Boiler of 18 kW

Abstract: The differences in the pollutant emissions from the combustion of bituminous coal and biofuels (wood, straw, and miscanthus pellets) under real-world boiler operating conditions were investigated. The experiments were performed on an experimental installation that comprised an 18 kW boiler, used in domestic central heating systems, equipped with a retort furnace, an automatic fuel feeder, a combustion air fan, and a fuel storage bin. The emission factors of gaseous pollutants, particulate matter, organic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…EFs in the literature vary largely, ,, and EFs found in the present study agree with earlier findings. For coal combustion in European appliances, Czaplicka et al reported EFs of approximately 190 mg MJ –1 , being approximately twice as high as EFs found here with 100 ± 10 mg MJ –1 , although the fuel-S content was comparable. Křůmal et al reported EFs of 143 to 658 mg MJ –1 for various coals and coal briquettes, with EFs of their brown coal briquettes being most comparable to EFs found in the present study.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…EFs in the literature vary largely, ,, and EFs found in the present study agree with earlier findings. For coal combustion in European appliances, Czaplicka et al reported EFs of approximately 190 mg MJ –1 , being approximately twice as high as EFs found here with 100 ± 10 mg MJ –1 , although the fuel-S content was comparable. Křůmal et al reported EFs of 143 to 658 mg MJ –1 for various coals and coal briquettes, with EFs of their brown coal briquettes being most comparable to EFs found in the present study.…”
Section: Discussioncontrasting
confidence: 49%
“…For residential coal combustion, information on emissions from stoves relevant for European emission scenarios is scarce, since most of the research was focused on boilers, ,, which are generally larger and might have more efficient NO x reduction due to operational/technological aspects . To the authors’ knowledge, NO x EFs for coal combustion in stoves relevant for Europe were only reported for coal briquettes from various coals by Mitchell et al varying from 204 to 438 mg MJ –1 , which are clearly higher than any of the other EFs found for biomass.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the combustion processes of solid fuels or their mixtures, significant amounts of organic compounds, such as volatile organic compounds (VOCs), polycyclic aromatic hydrocarbons (PAHs), phenols, and aliphatic compounds are emitted to the atmosphere as a result of incomplete combustion [13][14][15][16][17]. PAHs can naturally occur in coal and coal 2 of 15 combustion fly ashes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2021, 14, x FOR PEER REVIEW 2 of 15 hydrocarbons (PAHs), phenols, and aliphatic compounds are emitted to the atmosphere as a result of incomplete combustion [13][14][15][16][17]. PAHs can naturally occur in coal and coal combustion fly ashes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%